Seals, fish, humans and parasites in the Baltic: ecology, evolution and history - Buchmann, Kurt (Folia parasitologica, 2023)
Evolutionary and ecological processes affecting the interactions between hosts and parasites in the aquatic environment are at display in the Baltic Sea, a young and ecologically unstable marine ecosystem, where fluctuating abiotic and biotic factors affect the parasitofauna in fish. The dynamic infections of Baltic cod, a subpopulation of the Atlantic cod (Gadus morhua Linnaeus), with third stage anisakid nematode larvae of Pseudoterranova decipiens (Krabbe, 1878) and Contracaecum osculatum (Rudolphi, 1802) have increased following a significant increase of the Baltic grey seal Halichoerus grypus (Fabricius) population in the region. Cod serves as a paratenic host and marine mammals, pinnipeds, are definitive hosts releasing parasite eggs, with faeces, to the marine environment, where embryonation and hatching of the third stage larva take place. The parasite has no obligate intermediate hosts, but various invertebrates, smaller fish and cod act as paratenic hosts transmitting the infection to the seal. Contracaecum osculatum has an impact on the physiological performance of the cod, which optimises transmission of the larva from fish to seal. Thus, a muscle mass decrease of nearly 50% may result from heavy C. osculatum infections, probably amplified by a restricted food availability. The muscle atrophy is likely to reduce the escape reactions of the fish when meeting a foraging seal. In certain regions, where fish and seals are restricted in their migration patterns, such as the semi-enclosed Baltic Sea, the predation may contribute to a severe cod stock depletion. The parasites are zoonotic and represent a human health risk, when consumers ingest insufficiently heat- or freeze-treated infected products. Marked infections of the cod were previously reported during periods with elevated seal populations (late 19th and middle 20th century) and various scenarios for management of risk factors are evaluated in an evolutionary context.
Keywords: zoonosis; Baltic Sea; Ascaridoidea; Fish Diseases; Ecosystem; tuleňovití; Contracaecum; paraziti; Pseudoterranova; ryby; Fishes; larva; Animals; lidé; Humans; zvířata; nemoci ryb; ekosystém; Gadus morhua; Larva; fish stocks; Parasites; Seals, Earless